A elaboração do discurso no Romancero Gitano de Castelnuovo-Tedesco / Lorca - Rocha Júnior, Atilio Goltardo da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In the present work our aim was to reflect on some of the various extra musical and interdisciplinary procedures involved in the confection of the musical work Romancero Gitano, Mario Castelnuovo-Tedesco's authorship, with texts by Federico Garcia Lorca. To achieve this aim we have considered procedures such as rhetoric and word-painting, as well as research on biographical data about composer and poet, technical -musical analysis of each one of the movements of the work and poetical readings of the texts

No presente trabalho buscamos refletir a respeito de alguns dos diversos procedimentos extramusicais e interdisciplinares envolvidos na confecção da obra musical Romancero Gitano, de Autoria de Mario Castelnuovo-Tedesco com textos de Federico Garcia Lorca. Para o cumprimento desta tarefa foram considerados procedimentos como retórica e word-painting, bem como levantamento de dados biográficos de compositor e poeta, análises técnico -musicais de cada um dos movimentos da obra e leituras poéticas dos textos
Keywords: Castelnuovo-Tedesco, Mario 1895-1968; Garcia Lorca, Federico 1898-1936; Música e retórica; Violão; Musica coral; Musica e literatura; Music and rhetoric